Reaction pathways, proton transfer, and proton pumping in ba3 class cytochrome c oxidase: perspectives from DFT quantum chemistry and molecular dynamics - Noodleman, Louis; Götz, Andreas W.; Han Du, Wen-Ge; Hunsicker-Wang, Laura (Frontiers in Chemistry, 2023)
After drawing comparisons between the reaction pathways of cytochrome c oxidase (CcO, Complex 4) and the preceding complex cytochrome bc1 (Complex 3), both being proton pumping complexes along the electron transport chain, we provide an analysis of the reaction pathways in bacterial ba3 class CcO, comparing spectroscopic results and kinetics observations with results from DFT calculations. For an important arc of the catalytic cycle in CcO, we can trace the energy pathways for the chemical protons and show how these pathways drive proton pumping of the vectorial protons. We then explore the proton loading network above the Fe heme a3–CuB catalytic center, showing how protons are loaded in and then released by combining DFT-based reaction energies with molecular dynamics simulations over states of that cycle. We also propose some additional reaction pathways for the chemical and vector protons based on our recent work with spectroscopic support.